High-strength composite ceramic and preparation method thereof

By exchanging modified montmorillonite with magnesium oxide and calcium oxide, a sintering aid with interlayer structure is formed, which solves the problem of uneven dispersion of sintering aid during ceramic sintering, and significantly improves the strength and density of the ceramic.

CN119661206AInactive Publication Date: 2025-03-21XI'AN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510154927.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the sintering process of existing ceramics, it is difficult to disperse the sintering aid evenly, resulting in poorer density and overall strength of the ceramics.

Method used

By exchanging the modified montmorillonite with magnesium oxide and calcium oxide, an interlayer structure is formed as a sintering aid, and it is evenly dispersed into the ceramic powder through specific process steps. The interlayer structure of montmorillonite releases the sintering aid during the sintering process to promote the sintering of the ceramic.

Benefits of technology

The uniform dispersion of the sintering additive is achieved, the flexural strength, fracture toughness and hardness of the ceramic are improved, and high-strength composite ceramics are formed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661206A_ABST
    Figure CN119661206A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite ceramic preparation, in particular to high-strength composite ceramic and a preparation method thereof.The preparation method comprises the following steps that S1, graphene is subjected to acid treatment to prepare a graphene mixed solution; s2, preparing a mixture A containing ceramic powder; s3, preparing a mixture B containing modified montmorillonite; s4, uniformly mixing the mixture A, the mixture B and the graphene mixed solution to obtain slurry; and S5, pressing the slurry obtained in the step S4 into a ligand, and carrying out high-temperature sintering to obtain the composite ceramic. According to the invention, by adding the modified montmorillonite, the sintering aid growing between layers can be uniformly distributed in the whole ceramic powder, the regulation and control performance on ceramic sintering is good, the compactness of the ceramic is promoted, and the strength of the sintered ceramic is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite ceramic preparation, in particular to a high-strength composite ceramic and a preparation method thereof. Background Art

[0002] Ceramics have excellent properties such as high strength, high hardness, high temperature resistance, wear resistance, and corrosion resistance. They are widely used in aerospace, machinery, medical, energy and other fields. Ceramics are generally formed by sintering ceramic powders. Common ceramic powders include alumina ceramic powders, silicon carbide ceramic powders, etc. These ceramic powders require the addition of sintering aids during the sintering process. Sintering aids are also called sintering aids. When sintering aids can form a solid solution with the sintered material, the lattice will be distorted and activated, so the sintering temperature can be reduced, and the diffusion and sintering speeds can be increased. This is particularly strong for the formation of vacancy-type or interstitial-type solid solutions.

[0003] In the modern ceramic sintering process, metal oxides are generally selected as sintering aids, and these ceramic aids are added to the ceramic powder together, and the ceramic aids and the ceramic powder are evenly mixed by grinding. However, since the amount of sintering aid added is generally small, it is difficult to evenly disperse it into the entire ceramic powder by grinding, resulting in poor sintering control effect of the sintering aid on the ceramic, reducing the density and overall strength of the sintered ceramic. To this end, in response to the problems raised in the above background technology, a person skilled in the art has proposed a high-strength composite ceramic and a preparation method thereof. Summary of the invention

[0004] The object of the present invention is to provide a high-strength composite ceramic and a preparation method thereof to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions: A method for preparing high-strength composite ceramics, comprising the following steps: S1, placing graphene in a mixed acid of 98wt% concentrated sulfuric acid and 68wt% concentrated nitric acid and heating to 60-90°C for 8-15h, then filtering and washing with sufficient deionized water, dispersing the washed graphene in a mixed solution of polyvinyl alcohol and deionized water to obtain a graphene mixed solution; S2, dispersing the ceramic powder into a mixed solution of 30wt% hydrogen peroxide and 0.3mol / L γ-aminopropyltrimethoxysilane and soaking for 3-5h, filtering and washing the product with sufficient deionized water, and then dispersing the ceramic powder into a mixed solution of ethanol and deionized water to obtain a mixture A; S3, dispersing the modified montmorillonite in a mixed solution of ethanol and deionized water to obtain a mixture B; S4, adding the mixture B in step S3 to the mixture A obtained in step S2, stirring for 20-30 minutes to mix evenly, then adding the graphene mixed solution obtained in step S1 to the mixture A, continuing to stir for 30-60 minutes to mix evenly, heating to 120-140° C. to evaporate and remove part of the deionized water and ethanol, to obtain a mixed slurry; S5. Press the mixed slurry obtained in step S4 into a body at a pressure of 2-10 MPa. Sinter the body at 900-1350° C. and keep it warm for 0.5-2 h. Then heat it to 1400-1600° C. and sinter it and keep it warm for 1-4 h to obtain a high-strength composite ceramic.

[0006] Furthermore, in step S1, the mass ratio of graphene to the mixed acid of concentrated nitric acid and concentrated sulfuric acid is 1:(15-25), the mass ratio of concentrated nitric acid to concentrated sulfuric acid is 1:1, and the mass ratio of graphene, polyvinyl alcohol and deionized water is 1:(2-3):(45-60).

[0007] Furthermore, in step S2, the mass ratio of the ceramic powder to the mixed solution of hydrogen peroxide and γ-aminopropyltrimethoxysilane is 1:(8-10), the mass ratio of the ceramic powder, ethanol and deionized water in the mixture A is 1:(1.8-3.2):(1.6-2.5), the ceramic powder is composed of zirconium oxide powder, silicon carbide powder and aluminum oxide powder, the particle sizes of zirconium oxide powder, silicon carbide powder and aluminum oxide powder are all 1-15 μm, and the mass ratio of zirconium oxide powder, silicon carbide powder and aluminum oxide powder is 1:(0.6-1.2):(2.4-3.2).

[0008] Furthermore, the mass ratio of the modified montmorillonite, ethanol and deionized water in the mixture B of step S3 is 1:(2-5):(3-8).

[0009] Furthermore, the mass ratio of the graphene used in step S1, the ceramic powder used in step S2 and the modified montmorillonite used in step S3 is 1:(90-120):(4-12); the mass ratio of the mixed slurry obtained in step S4 to the ceramic powder is (1.5-2.2):1.

[0010] Furthermore, the modified montmorillonite is prepared by the following steps: S101, soaking the montmorillonite in a 1-3 mol / L hydrochloric acid solution for 1-2 h, filtering the filtered product, washing it with a sufficient amount of deionized water, and then heat-preserving it at 100-300° C. for 1-4 h to obtain a pre-treated montmorillonite; S102, soaking the pretreated montmorillonite in step S101 in a mixed solution of 0.2-0.8 mol / L triacetamidomethylammonium sulfate, 0.5-0.8 mol / L sodium chloride and 0.2-0.6 mol / L aluminum nitrate for 0.5-1.5 h, pressurizing during the soaking process, the pressure being 1-5 MPa, filtering after soaking, and washing the filtered product with sufficient deionized water and drying to obtain the pretreated montmorillonite; S103, adding the pretreated montmorillonite obtained in step S102 to a mixed solution of 0.01-0.1 molL calcium chloride and 0.01-0.1 molL magnesium chloride and soaking it for 1.5-4 h, filtering and then soaking the filtered product in a sodium hydroxide solution with a pH of 10-11 for 2-4 h, filtering again and washing the filtered product with sufficient deionized water, and then calcining at 300-500° C. for 1-3 h to obtain modified montmorillonite.

[0011] Furthermore, in step S101, the mass ratio between montmorillonite and the hydrochloric acid solution is 1:(15-30), and the particle size of the montmorillonite soaked in the hydrochloric acid solution is 1-5 μm.

[0012] Furthermore, in step S102, the mass ratio between the pre-treated montmorillonite and the mixed solution of triacetamidomethylammonium sulfate, sodium chloride and aluminum nitrate is 1:(20-30).

[0013] Furthermore, in step S103, the mass ratio of the pretreated montmorillonite to the mixed solution of calcium chloride and magnesium chloride is 1:(40-80), and the mass ratio of the pretreated montmorillonite to the sodium hydroxide solution is 1:(20-30).

[0014] A high-strength composite ceramic is prepared by the preparation method of the high-strength composite ceramic according to any one of claims 1 to 9.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses the particularity of ion exchange in the interlayer structure of montmorillonite to exchange magnesium ions and calcium ions between its layers, and then synthesizes magnesium oxide and calcium oxide in the layers of montmorillonite by adjusting pH and calcining. Magnesium oxide and calcium oxide can be used as ceramic sintering aids. The sintering aid particles are smaller. During the temperature-raising sintering process, the interlayer structure of montmorillonite is destroyed, and the sintering aid overflows, which has a stronger sintering promoting effect on the ceramic and is conducive to forming a composite ceramic with higher strength. 2. In the present invention, the montmorillonite carries the sintering aid into the entire ceramic slurry and is evenly dispersed with the treated ceramic powder. Even a relatively small amount of sintering aid can be evenly dispersed in the entire ceramic slurry, which reduces the grinding and dispersion time, and the sintered ceramic has higher strength; 3. The ceramic powder in the present invention comprises a variety of powder compositions, wherein the graphene and ceramic powders are both pre-treated, and the overall bending strength, fracture toughness and hardness of the sintered ceramics are effectively improved. The processing method is simple and suitable for promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a process flow chart for preparing high-strength composite ceramics in the present invention; Figure 2 The process flow chart of preparing modified montmorillonite in the present invention is shown in FIG. DETAILED DESCRIPTION

[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] See also Figure 1 to Figure 2 , the present invention provides:

[0019] Example 1 A method for preparing high-strength composite ceramics, comprising the following steps: S1, putting 0.53g of graphene into a mixed acid of 98wt% concentrated sulfuric acid and 68wt% concentrated nitric acid with a total mass of 10.6g and heating to 75°C for 12h, wherein the mass ratio of concentrated nitric acid to concentrated sulfuric acid is 1:1, and then filtering and washing with sufficient deionized water, dispersing the washed graphene into a mixed solution containing 1.32g of polyvinyl alcohol and 26.5g of deionized water to obtain a graphene mixed solution; S2, dispersing 10.6g of zirconium oxide powder, 10.6g of silicon carbide powder and 31.8g of aluminum oxide powder into a mixed solution of 470g of 30wt% hydrogen peroxide and 0.3mol / L γ-aminopropyltrimethoxysilane and soaking for 4h, the particle size of zirconium oxide powder, silicon carbide powder and aluminum oxide powder are all 5μm, filtering and washing the product with sufficient deionized water, and then dispersing zirconium oxide powder, silicon carbide powder and aluminum oxide powder into a mixed solution of 127.2g of ethanol and 116.6g of deionized water to obtain a mixture A; S3, dispersing 3.18 g of modified montmorillonite into a mixed solution of 12.7 g of ethanol and 15.9 g of deionized water to obtain a mixture B; S4, adding the mixture B in step S3 to the mixture A obtained in step S2, stirring for 26 minutes to mix evenly, then adding the graphene mixed solution obtained in step S1 to the mixture A, continuing to stir for 55 minutes to mix evenly, heating to 130° C. to evaporate and remove part of the deionized water and ethanol, to obtain 90.1 g of mixed slurry; S5. The mixed slurry obtained in step S4 is pressed into a body at a pressure of 5 MPa. The body is first sintered at 1000° C. and kept warm for 0.5-2 h, and then heated to 1500° C. and sintered and kept warm for 2 h to obtain a high-strength composite ceramic.

[0020] The modified montmorillonite is prepared by the following steps: S101, 4.25 g of montmorillonite with a particle size of 2 μm is placed in 85 g of a 2 mol / L hydrochloric acid solution and soaked for 1.4 h, filtered, and the filtered product is washed with sufficient deionized water and then kept at 250° C. for 3 h to obtain a pre-treated montmorillonite; S102, soaking 4.16g of the pre-treated montmorillonite obtained in step S101 in a mixed solution of 0.6mol / L triacetamidomethylammonium sulfate, 0.7mol / L sodium chloride and 0.4mol / L aluminum nitrate for 1.2h, wherein the mass of the mixed solution of triacetamidomethylammonium sulfate, sodium chloride and aluminum nitrate is 104g, and pressurizing is performed during the soaking process, and the pressurizing size is 3MPa. After soaking, filtering is performed, and the filtered product is washed with sufficient deionized water and dried to obtain the pre-treated montmorillonite; S103, adding 3.54g of pretreated montmorillonite obtained in step S102 into a mixed solution of 0.03molL calcium chloride and 0.06molL magnesium chloride and soaking it for 2h, the mass of the mixed solution of calcium chloride and magnesium chloride is 212g, filtering and then soaking the filtered product in 78g sodium hydroxide solution with a pH of 10 for 3h, filtering again and washing the filtered product with sufficient deionized water, and then calcining at 450°C for 2h to obtain modified montmorillonite.

[0021] Example 2 A method for preparing high-strength composite ceramics, comprising the following steps: S1, putting 0.46g of graphene into a mixed acid of 98wt% concentrated sulfuric acid and 68wt% concentrated nitric acid with a total mass of 6.9g and heating to 60°C for 8h, wherein the mass ratio of concentrated nitric acid to concentrated sulfuric acid is 1:1, and then filtering and washing with sufficient deionized water, dispersing the washed graphene into a mixed solution of 0.92g polyvinyl alcohol and 20.7g deionized water to obtain a graphene mixed solution; S2, 10.35g of zirconium oxide powder, 6.21g of silicon carbide powder and 24.84g of aluminum oxide powder were dispersed in a mixed solution of 331.2g of 30wt% hydrogen peroxide and 0.3mol / L γ-aminopropyltrimethoxysilane and immersed for 3h, the particle size of zirconium oxide powder, silicon carbide powder and aluminum oxide powder were all 1μm, filtered and the product was washed with sufficient deionized water, and then zirconium oxide powder, silicon carbide powder and aluminum oxide powder were dispersed in a mixed solution of 74.52g of ethanol and 66.24g of deionized water to obtain mixture A; S3, dispersing 1.84 g of modified montmorillonite into a mixed solution of 3.68 g of ethanol and 5.52 g of deionized water to obtain a mixture B; S4, adding the mixture B in step S3 to the mixture A obtained in step S2, stirring for 20 minutes to mix evenly, then adding the graphene mixed solution obtained in step S1 to the mixture A, continuing to stir for 30 minutes to mix evenly, heating to 120° C. to evaporate and remove part of the deionized water and ethanol, to obtain 62.1 g of mixed slurry; S5. The mixed slurry obtained in step S4 is pressed into a body at a pressure of 2 MPa. The body is first sintered at 900° C. and kept warm for 0.5 h, and then heated to 1400° C. and sintered and kept warm for 1 h to obtain a high-strength composite ceramic.

[0022] The modified montmorillonite is prepared by the following steps: S101, 2.35 g of montmorillonite with a particle size of 1 μm is placed in 35.25 g of a hydrochloric acid solution with a concentration of 1 mol / L and soaked for 1 hour, the filtered product is washed with sufficient deionized water and then kept at 100° C. for 1 hour to obtain a pre-treated montmorillonite; S102, soaking the 2.16g pre-treated montmorillonite obtained in step S101 in a mixed solution of 0.2mol / L triacetamidomethylammonium sulfate, 0.5mol / L sodium chloride and 0.2mol / L aluminum nitrate for 0.5h, wherein the mass of the mixed solution of triacetamidomethylammonium sulfate, sodium chloride and aluminum nitrate is 43.2g, and pressurizing is performed during the soaking process, and the pressure is 1MPa. After soaking, filtering is performed, and the filtered product is washed with sufficient deionized water and dried to obtain the pre-treated montmorillonite; S103, adding 1.98g of the pretreated montmorillonite obtained in step S102 to a mixed solution of 0.01molL calcium chloride and 0.01molL magnesium chloride and soaking it for 1.5h, the mass of the mixed solution of calcium chloride and magnesium chloride is 79.2g, filtering and then soaking the filtered product in 39.6g of sodium hydroxide solution with a pH of 10 for 2h, filtering again and washing the filtered product with sufficient deionized water, and then calcining at 300°C for 1h to obtain modified montmorillonite.

[0023] Example 3 A method for preparing high-strength composite ceramics, comprising the following steps: S1, putting 0.38g of graphene into a mixed acid of 98wt% concentrated sulfuric acid and 68wt% concentrated nitric acid with a total mass of 9.5g and heating to 90°C for 15h, wherein the mass ratio between concentrated nitric acid and concentrated sulfuric acid is 1:1, and then filtering and washing with sufficient deionized water, dispersing the washed graphene into a mixed solution of 1.14g of polyvinyl alcohol and 22.8g of deionized water to obtain a graphene mixed solution; S2, 8.44g of zirconium oxide powder, 10.13g of silicon carbide powder and 27.01g of aluminum oxide powder were dispersed in a mixed solution of 456g of 30wt% hydrogen peroxide and 0.3mol / L γ-aminopropyltrimethoxysilane and soaked for 5h, the particle size of zirconium oxide powder, silicon carbide powder and aluminum oxide powder were all 15μm, filtered and the product was washed with sufficient deionized water, and then the zirconium oxide powder, silicon carbide powder and aluminum oxide powder were dispersed in a mixed solution of 145.92g of ethanol and 114g of deionized water to obtain a mixture A; S3, dispersing 4.56 g of modified montmorillonite into a mixed solution of 22.8 g of ethanol and 36.48 g of deionized water to obtain a mixture B; S4, adding the mixture B in step S3 to the mixture A obtained in step S2, stirring for 30 minutes to mix evenly, then adding the graphene mixed solution obtained in step S1 to the mixture A, continuing to stir for 60 minutes to mix evenly, heating to 140° C. to evaporate and remove part of the deionized water and ethanol, to obtain 100.3 g of mixed slurry; S5. The mixed slurry obtained in step S4 is pressed into a body at a pressure of 10 MPa. The body is first sintered at 1350° C. and kept warm for 2 hours, and then heated to 1600° C. and sintered and kept warm for 4 hours to obtain a high-strength composite ceramic.

[0024] The modified montmorillonite is prepared by the following steps: S101, 5.87 g of montmorillonite with a particle size of 5 μm was placed in 176.1 g of a 3 mol / L hydrochloric acid solution and soaked for 2 h, filtered, and the filtered product was washed with sufficient deionized water and then kept at 300° C. for 4 h to obtain pre-treated montmorillonite; S102, soaking 5.46g of the pre-treated montmorillonite obtained in step S101 in a mixed solution of 0.8mol / L triacetamidomethylammonium sulfate, 0.8mol / L sodium chloride and 0.6mol / L aluminum nitrate for 1.5h, wherein the mass of the mixed solution of triacetamidomethylammonium sulfate, sodium chloride and aluminum nitrate is 163.8g, and pressurizing is performed during the soaking process, and the pressurizing size is 5MPa. After soaking, filtering is performed, and the filtered product is washed with sufficient deionized water and dried to obtain the pre-treated montmorillonite; S103, adding 4.93g of pretreated montmorillonite obtained in step S102 to a mixed solution of 0.1molL calcium chloride and 0.1molL magnesium chloride and soaking for 4h, the mass of the mixed solution of calcium chloride and magnesium chloride is 394.4g, filtering and then soaking the filtered product in 147.9g sodium hydroxide solution with a pH of 11 for 4h, filtering again and washing the filtered product with sufficient deionized water, and then calcining at 500°C for 3h to obtain modified montmorillonite.

[0025] Example 4 A method for preparing high-strength composite ceramics, comprising the following steps: S1, putting 0.44g of graphene into a mixed acid of 98wt% concentrated sulfuric acid and 68wt% concentrated nitric acid with a total mass of 8.8g and heating to 80°C for 14h, wherein the mass ratio between concentrated nitric acid and concentrated sulfuric acid is 1:1, and then filtering and washing with sufficient deionized water, dispersing the washed graphene into a mixed solution of 1.11 polyvinyl alcohol and 24.2g deionized water to obtain a graphene mixed solution; S2, 11g of zirconium oxide powder, 8.8g of silicon carbide powder and 28.6g of aluminum oxide powder were dispersed in a mixed solution of 435g of 30wt% hydrogen peroxide and 0.3mol / L γ-aminopropyltrimethoxysilane and immersed for 4.2h, the particle size of zirconium oxide powder, silicon carbide powder and aluminum oxide powder were all 10μm, filtered and the product was washed with sufficient deionized water, and then the zirconium oxide powder, silicon carbide powder and aluminum oxide powder were dispersed in a mixed solution of 125.8g of ethanol and 112.6g of deionized water to obtain a mixture A; S3, dispersing 2.56 g of modified montmorillonite into a mixed solution of 10.24 g of ethanol and 16.92 g of deionized water to obtain a mixture B; S4, adding the mixture B in step S3 to the mixture A obtained in step S2, stirring for 28 minutes to mix evenly, then adding the graphene mixed solution obtained in step S1 to the mixture A, continuing to stir for 48 minutes to mix evenly, heating to 120°C to evaporate and remove part of the deionized water and ethanol, to obtain 87g of mixed slurry; S5. The mixed slurry obtained in step S4 is pressed into a green body at a pressure of 7 MPa. The green body is first sintered at 1200° C. and kept warm for 1.8 h, and then heated to 1600° C. and sintered and kept warm for 3.6 h to obtain a high-strength composite ceramic.

[0026] The modified montmorillonite is prepared by the following steps: S101, 3.16 g of montmorillonite with a particle size of 4 μm is placed in 79 g of a 2.2 mol / L hydrochloric acid solution and soaked for 1.5 h, filtered, and the filtered product is washed with sufficient deionized water and then kept at 100-300° C. for 1-4 h to obtain pre-treated montmorillonite; S102, soaking 3.07g of the pre-treated montmorillonite obtained in step S101 in a mixed solution of 0.6mol / L triacetamidomethylammonium sulfate, 0.8mol / L sodium chloride and 0.4mol / L aluminum nitrate for 1.1h, wherein the mass of the mixed solution of triacetamidomethylammonium sulfate, sodium chloride and aluminum nitrate is 65.7g, and pressurizing is performed during the soaking process, and the pressurizing size is 3MPa. After soaking, filtering is performed, and the filtered product is washed with sufficient deionized water and dried to obtain the pre-treated montmorillonite; S103, adding 2.78g of pretreated montmorillonite obtained in step S102 to a mixed solution of 0.08molL calcium chloride and 0.05molL magnesium chloride and soaking for 2.8h, the mass of the mixed solution of calcium chloride and magnesium chloride is 153.9g, filtering and then soaking the filtered product in 68.5g sodium hydroxide solution with a pH of 11 for 3.2h, filtering again and washing the filtered product with sufficient deionized water, and then calcining at 400°C for 1.8h to obtain modified montmorillonite.

[0027] The particle sizes of the zirconium oxide powder, silicon carbide powder and aluminum oxide powder used in Examples 1-4 of the present invention are all 1-15 μm, and the particle size of the montmorillonite soaked in the hydrochloric acid solution in step S101 in Examples 1-4 of the present invention is 1-5 μm.

[0028] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that step S103 is cancelled, and in step S3, the same weight of pretreated montmorillonite as the modified montmorillonite in Example 1 is directly added, and 0.5 g of magnesium oxide and calcium oxide with a mass ratio of 1:1 are also added. After evaporating the same deionized water and ethanol as in Example 1, the mixture is ground and dispersed for 2 hours, and the remaining steps are exactly the same as in Example 1.

[0029] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that step S103 is cancelled, and in step S3, the same weight of pretreated montmorillonite as the modified montmorillonite in Example 1 is directly added, and 1.5 g of magnesium oxide and calcium oxide with a mass ratio of 1:1 are also added. After evaporating the same deionized water and ethanol as in Example 1, the mixture is ground and dispersed for 2 hours, and the remaining steps are exactly the same as in Example 1.

[0030] Comparative Example 3 The difference between Comparative Example 2 and Example 1 is that step S103 is cancelled, and in step S3, the same weight of pretreated montmorillonite as the modified montmorillonite in Example 1 is directly added, and 3.0 g of magnesium oxide and calcium oxide with a mass ratio of 1:1 are also added. After evaporating the same deionized water and ethanol as in Example 1, the mixture is ground and dispersed for 2 hours, and the remaining steps are exactly the same as in Example 1.

[0031] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the process of soaking the zirconium oxide powder, silicon carbide powder and aluminum oxide powder in a mixed solution of 30wt% hydrogen peroxide and 0.3mol / L γ-aminopropyltrimethoxysilane in step S2 is cancelled, and the remaining steps are exactly the same as in Example 1.

[0032] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the treatment process of graphene with concentrated sulfuric acid and concentrated nitric acid in step S1 is cancelled, and the remaining steps are exactly the same as those in Example 1.

[0033] 9 groups of composite ceramics were prepared by Examples 1-4 and Comparative Examples 1-5, and the performance of the composite ceramics prepared by these 9 groups of implementation methods was tested. The flexural strength (MPa) was measured by the three-point bending method, and the fracture toughness (MPa·m 1 / 2 ) was measured by the single-side notched beam method, and the hardness (Hv) was measured by the ASTM E384-17 nanoindentation method. The test results are shown in Table 1 below: Table 1: Test table of flexural strength, fracture toughness and hardness of 9 groups of composite ceramics prepared in Examples 1-4 and Comparative Examples 1-5 Flexural strength(MPa) Hardness(Hv) <![CDATA[Fracture toughness (MPa·m 1 / 2 )]]> Example 1 528 1642 7.9 Example 2 496 1589 7.4 Example 3 487 1613 7.8 Example 4 531 1627 7.9 Comparative Example 1 447 1485 6.7 Comparative Example 2 481 1559 7.2 Comparative Example 3 479 1564 7.2 Comparative Example 4 472 1498 7.3 Comparative Example 5 444 1546 7.1 By comparing the data of Comparative Examples 1-3 and Example 1, it can be seen that in the present invention, after adding modified montmorillonite and loading calcium oxide and magnesium oxide between the montmorillonite layers, the sintering of the ceramic as a whole is promoted. Compared with directly adding sintering aids, the flexural strength, fracture toughness and hardness of the obtained composite ceramic are significantly improved; the flexural strength, fracture toughness and hardness of the composite ceramic in Comparative Example 2 are greatly improved compared with those in Comparative Example 1, reflecting that increasing the amount of sintering aid can promote the sintering strength of the ceramic, and the flexural strength, fracture toughness and hardness of the composite ceramic in Comparative Example 3 are not much different from those in Comparative Example 2, reflecting that when the amount of sintering aid reaches a certain level, increasing the amount of sintering aid used does not have a strong effect on promoting the sintering of the ceramic; in addition, the acid leaching treatment of graphene in step S1 and the pre-treatment of ceramic powder in step S2 in the present invention also improve the flexural strength, fracture toughness and hardness of the composite ceramic.

[0034] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a high-strength composite ceramic, characterized in that: Prepared by the following steps: S1, placing graphene in a mixed acid of 98wt% concentrated sulfuric acid and 68wt% concentrated nitric acid and heating to 60-90°C for 8-15h, then filtering and washing with sufficient deionized water, dispersing the washed graphene in a mixed solution of polyvinyl alcohol and deionized water to obtain a graphene mixed solution; S2, dispersing the ceramic powder into a mixed solution of 30wt% hydrogen peroxide and 0.3mol / L γ-aminopropyltrimethoxysilane and soaking for 3-5h, filtering and washing the product with sufficient deionized water, and then dispersing the ceramic powder into a mixed solution of ethanol and deionized water to obtain a mixture A; S3, dispersing the modified montmorillonite in a mixed solution of ethanol and deionized water to obtain a mixture B; S4, adding the mixture B in step S3 to the mixture A obtained in step S2, stirring for 20-30 minutes to mix evenly, then adding the graphene mixed solution obtained in step S1 to the mixture A, continuing to stir for 30-60 minutes to mix evenly, heating to 120-140° C. to evaporate and remove part of the deionized water and ethanol, to obtain a mixed slurry; S5. Press the mixed slurry obtained in step S4 into a body at a pressure of 2-10 MPa. Sinter the body at 900-1350° C. and keep it warm for 0.5-2 h. Then heat it to 1400-1600° C. and sinter it and keep it warm for 1-4 h to obtain a high-strength composite ceramic.

2. The method for preparing the high-strength composite ceramic according to claim 1, characterized in that: In step S1, the mass ratio of graphene to the mixed acid of concentrated nitric acid and concentrated sulfuric acid is 1:(15-25), the mass ratio of concentrated nitric acid to concentrated sulfuric acid is 1:1, and the mass ratio of graphene, polyvinyl alcohol and deionized water is 1:(2-3):(45-60).

3. The method for preparing the high-strength composite ceramic according to claim 1, characterized in that: In the step S2, the mass ratio of the ceramic powder to the mixed solution of hydrogen peroxide and γ-aminopropyltrimethoxysilane is 1:(8-10), the mass ratio of the ceramic powder, ethanol and deionized water in the mixture A is 1:(1.8-3.2):(1.6-2.5), the ceramic powder is composed of zirconium oxide powder, silicon carbide powder and aluminum oxide powder, the particle sizes of zirconium oxide powder, silicon carbide powder and aluminum oxide powder are all 1-15 μm, and the mass ratio of zirconium oxide powder, silicon carbide powder and aluminum oxide powder is 1:(0.6-1.2):(2.4-3.2).

4. The method for preparing high-strength composite ceramics according to claim 1, characterized in that: The mass ratio of the modified montmorillonite, ethanol and deionized water in the mixture B of step S3 is 1:(2-5):(3-8).

5. The method for preparing high-strength composite ceramics according to claim 1, characterized in that: The mass ratio of the graphene used in step S1, the ceramic powder used in step S2 and the modified montmorillonite used in step S3 is 1:(90-120):(4-12); the mass ratio of the mixed slurry obtained in step S4 to the ceramic powder is (1.5-2.2):

1.

6. The method for preparing high-strength composite ceramics according to claim 1, characterized in that: The modified montmorillonite is prepared by the following steps: S101, soaking the montmorillonite in a 1-3 mol / L hydrochloric acid solution for 1-2 h, filtering the filtered product, washing it with a sufficient amount of deionized water, and then heat-preserving it at 100-300° C. for 1-4 h to obtain a pre-treated montmorillonite; S102, soaking the pretreated montmorillonite in step S101 in a mixed solution of 0.2-0.8 mol / L triacetamidomethylammonium sulfate, 0.5-0.8 mol / L sodium chloride and 0.2-0.6 mol / L aluminum nitrate for 0.5-1.5 h, pressurizing during the soaking process, the pressure being 1-5 MPa, filtering after soaking, and washing the filtered product with sufficient deionized water and drying to obtain the pretreated montmorillonite; S103, adding the pretreated montmorillonite obtained in step S102 to a mixed solution of 0.01-0.1 molL calcium chloride and 0.01-0.1 molL magnesium chloride and soaking it for 1.5-4 h, filtering and then soaking the filtered product in a sodium hydroxide solution with a pH of 10-11 for 2-4 h, filtering again and washing the filtered product with sufficient deionized water, and then calcining at 300-500° C. for 1-3 h to obtain modified montmorillonite.

7. The high-strength composite ceramic according to claim 6, characterized in that: In the step S101, the mass ratio between montmorillonite and the hydrochloric acid solution is 1:(15-30), and the particle size of the montmorillonite soaked in the hydrochloric acid solution is 1-5 μm.

8. The high-strength composite ceramic according to claim 6, characterized in that: In the step S102, the mass ratio between the pre-treated montmorillonite and the mixed solution of triacetamidomethylammonium sulfate, sodium chloride and aluminum nitrate is 1:(20-30).

9. The high-strength composite ceramic according to claim 6, characterized in that: In step S103, the mass ratio of the pretreated montmorillonite to the mixed solution of calcium chloride and magnesium chloride is 1:(40-80), and the mass ratio of the pretreated montmorillonite to the sodium hydroxide solution is 1:(20-30).

10. A high-strength composite ceramic, characterized in that: The high-strength composite ceramic is prepared by the preparation method of any one of claims 1 to 9.